Developmental asynchrony and antagonism of sex determination pathways in a lizard with temperature-induced sex reversal - Sarah L. Whiteley; Vera Weisbecker; Arthur Georges; Arnault Roger Gaston Gauthier; Darryl L. Whitehead; Clare E. Holleley (Scientific Reports, 2018)
Abstract Vertebrate sex differentiation follows a conserved suite of developmental events: the bipotential gonads differentiate and shortly thereafter sex specific traits become dimorphic. However, this may not apply to squamates, a diverse vertebrate lineage comprising of many species with thermosensitive sexual development. Of the three species with data on the relative timing of gonad differentiation and genital dimorphism, the females of two (Niveoscincus ocellatus and Barisia imbricata) exhibit a phase of temporary pseudohermaphroditism or TPH (gonads have differentiated well before genital dimorphism). We report a third example of TPH in Pogona vitticeps, an agamid with temperature-induced male to female sex reversal. These findings suggest that for female squamates, genital and gonad development may not be closely synchronised, so that TPH may be common. We further observed a high frequency of ovotestes, a usually rare gonadal phenotype characterised by a mix of male and female structures, exclusively associated with temperature-induced sex reversal. We propose that ovotestes are evidence of a period of antagonism between male and female sex-determining pathways during sex reversal. Female sexual development in squamates is considerably more complex than has been appreciated, providing numerous avenues for future exploration of the genetic and hormonal cues that govern sexual development.